KETERLIBATAN MASYARAKAT LOKAL DALAM UPAYA PENGEMBANGAN EKOWISATA MANGROVE KALI LAMONG - Nurhasanah, Winda; Hardjati, Susi (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine and describe community participation through the development of Mangrove Ecotourism Kali Lamong in Sukorejo Village, Kebomas District, Gresik Regency. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The main focus of the research is the form of community participation classified by Cohen and Uphoff which consists of participation in decision making, participation in implementation, participation in benefit, and participation in evaluation. The results showed that the people of Sukorejo Village had actively participated in the development of Kali Lamong Mangrove Ecotourism, starting from decision making where the community provided ideas and suggestions in meetings. Contributing to the implementation process with labor, but not contributing with money and materials. Taking benefits both economically and environmentally, and being involved in evaluation activities to assess Kali Lamong Mangrove Ecotourism. Overall, the community has participated in three research focus areas, while one research focus remains unfulfilled, as the sub-focus on contributions in the form of money and materials does not indicate any involvement.